PERSEPSI GURU PADA KESESUAI ISI PADA BUKU KURIKULUM MERDEKA SD NEGERI 2 LAKEA - Ramlawati S. Maruna; Moh Ridini; Nasriani (STKIP Subang, 2025)
This study is motivated by concerns about the heavy material of the Merdeka Curriculum book, especially for elementary school students. Therefore, the purpose of this study is to determine the teacher's perception of the suitability of the content of the Merdeka Curriculum book at State Elementary School (SDN) 2 Lakea. To achieve this goal, this study used a qualitative approach with the research subject being the homeroom teacher of SDN 2 Lakea. Data were collected through interviews, observations, and documentation. The results showed that teachers' perceptions of the suitability of the content of the Merdeka Curriculum book, as measured by indicators of absorption of stimuli or objects, understanding or understanding, and assessment or evaluation, were well implemented. Overall, the teacher's perception of the suitability of the content of the Merdeka Curriculum book at SDN 2 Lakea shows positive results, which means that the content of the book is appropriate. These results indicate that the material in the Merdeka Curriculum book is appropriate and can be well received by teachers as the main users of the book. However, further research involving students as research subjects is needed. This is important to get a more comprehensive picture of the suitability of the contents of the Merdeka Curriculum book from various perspectives